Lisa Pathfinder - Armano,M; Audley,H; Baird,J; Binetruy,P; Born,M; Bortoluzzi,D; Castelli,E; Cavalleri,A; Cesarini,A; Cruise,AM; Danzmann,K; De,Deus Silva M; et al. (2017)
© 2017 28th International Symposium on Lepton Photon Interactions at High Energies, LP 2017. All rights reserved. Since the 2017 Nobel Prize in Physics was awarded for the observation of gravitational waves, it is fair to say that the epoch of gravitational wave astronomy (GWs) has begun. However, a number of interesting sources of GWs can only be observed from space. To demonstrate the feasibility of the Laser Interferometer Space Antenna (LISA), a future gravitational wave observatory in space, the LISA Pathfinder satellite was launched on December, 3rd 2015. Measurements of the spurious forces accelerating an otherwise free-falling test mass, and detailed investigations of the individual subsystems needed to achieve the free-fall, have been conducted throughout the mission. This overview article starts with the purpose and aim of the mission, explains satellite hardware and mission operations and ends with a summary of selected important results and an outlook towards LISA. From the LISA Pathfinder experience, we can conclude that the proposed LISA mission is feasible.